A high frequency assessment of the ECB securities markets programme - Eric Ghysels; Julien Idier; Simone Manganelli; Olivier Vergote (European Central Bank (ECB), 2014)
Policy impact studies often suffer from endogeneity problems. Consider the case of the ECB Securities Markets Programme: If Eurosystem interventions were triggered by sudden and strong price deteriorations, looking at daily price changes may bias downwards the correlation between yields and the amounts of bonds purchased. Simple regression of daily changes in yields on quantities often give insignificant or even positive coefficients and therefore suggest that SMP interventions have been ineffective, or worse counterproductive. We use high frequency data on purchases of the ECB Securities Markets Programme and sovereign bond quotes to address the endogeneity issues. We propose an econometric model that considers, simultaneously, first and second conditional moments of market price returns at daily and intradaily frequency. We find that SMP interventions succeeded in reducing yields and volatility of government bond segments of the countries under the programme. Finally, the new econometric model is broadly applicable to market intervention studies.
Keywords: E52; E44; G12; C58; 330; component models; euro area crisis; high frequency data; SMP; unconventional monetary policy